The development of algorithm and programs of choice of class of architecture of software - Черныш, О. А. (Problems of Informatization and Control, 2007)
Different methods for the decision of a problem on own values are examined. The description of the modified method of the analysis of hierarchies in which own values are calculated by means of QR-algorithm with shift is given. Results of researches of the modified method of the analysis of hierarchies are presented<!--EndFragment--> ом. Представлены результаты исследований модифицированного метода анализа иерархий